2012
DOI: 10.1117/1.jbo.17.11.115005
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved singlet oxygen luminescence detection under photodynamic therapy relevant conditions: comparison ofex vivoapplication of two photosensitizer formulations

Abstract: Singlet oxygen plays a crucial role in photo-dermatology and photodynamic therapy (PDT) of cancer. Its direct observation by measuring the phosphorescence at 1270 nm, however, is still challenging due to the very low emission probability. It is especially challenging for the time-resolved detection of singlet oxygen kinetics in vivo which is of special interest for biomedical applications. Photosensitized generation of singlet oxygen, in pig ear skin as model for human skin, is investigated here. Two photosens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…3). The photocurrents were completely suppressed on N 2 purges, whether HQ was present or not, but recovered completely on admission of air, consistent with a Type II mechanism and the high 1 O 2 quantum yield ( Φ Δ ∼0.6 in acetone, methanol) previously reported for F 64 PcZn23242532. Intriguingly, for SPE|F 64 PcZn the anaerobic photocurrent (under N 2 ) exhibits a sign reversal in the presence of HQ, suggesting a direct electron transfer from HQ to F 64 PcZn and, eventually to the electrode, in agreement with a recent report on the direct photoreduction of F 64 PcZn by an electron donor in strictly oxygen-free conditions30.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…3). The photocurrents were completely suppressed on N 2 purges, whether HQ was present or not, but recovered completely on admission of air, consistent with a Type II mechanism and the high 1 O 2 quantum yield ( Φ Δ ∼0.6 in acetone, methanol) previously reported for F 64 PcZn23242532. Intriguingly, for SPE|F 64 PcZn the anaerobic photocurrent (under N 2 ) exhibits a sign reversal in the presence of HQ, suggesting a direct electron transfer from HQ to F 64 PcZn and, eventually to the electrode, in agreement with a recent report on the direct photoreduction of F 64 PcZn by an electron donor in strictly oxygen-free conditions30.…”
Section: Resultssupporting
confidence: 84%
“…The essential role of O 2 for substrate detection using the photodynamic effect observed for F 64 PcZn in solution2425 and ex vivo 2332, was confirmed by comparing photocurrents obtained in an air-saturated buffer with those obtained under an inert N 2 atmosphere (Fig. 3).…”
Section: Resultsmentioning
confidence: 64%
“…This extends work in photosensitizer solution, tumor cells in vitro and normal tissue (skin) in vivo, reported previously by ourselves 8,9 and by other groups [10][11][12]14 using variations on the SOLD instrumentation, measurement technique and biological models. The most direct comparison can be made with the in vivo study by Yamamoto et al, 13 in which 1 O 2 luminescence dosimetry was used in a gliosarcoma tumor xenograft model, assessing the PDT response by quantitative histopathology.…”
Section: Discussionsupporting
confidence: 79%
“…8 Importantly, this response curve is independent of the individual treatment parameters such as photosensitizer concentration, light dose and oxygenation. Its validity has also been demonstrated in normal skin models 9,10 and in normal human skin using a timeintegrated technique, 11,12 15 have shown that it may not work for all photosensitizers, depending on parameters such as the level of oxygenation.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] PDT involves three major components: light, PS and molecular oxygen. 7 Continuous-wave (CW) and pulsed lasers were widely used as excitation light sources for activating PS in PDT, and the e®ects of PS types, 8,9 oxygen concentration 10,11 on 1 O 2 production have been intensively evaluated, respectively. However, as one of the three essential components of PDT, the e®ects of laser parameters (i.e., pulse width, repetition rate) for pulsed lasers on the kinetics and production of 1 O 2 luminescence have not been fully explored.…”
Section: Introductionmentioning
confidence: 99%